2006
DOI: 10.1128/jvi.00781-06
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Amino Acid Residues within Simian Virus 40 Capsid Proteins Vp1, Vp2, and Vp3 That Are Required for Their Interaction and for Viral Infection

Abstract: Interaction of simian virus 40 (SV40) major capsid protein Vp1 with the minor capsid proteins Vp2 and Vp3is an integral aspect of the SV40 architecture. Two Vp3 sequence elements mediate Vp1 pentamer binding in vitro, Vp3 residues 155 to 190, or D1, and Vp3 residues 222 to 234, or D2. Of the two, D1 but not D2 was necessary and sufficient to direct the interaction with Vp1 in vivo. Rational mutagenesis of Vp3 residues (Phe157, Ile158, Pro164, Gly165, Gly166, Leu177, and Leu181) or Vp1 residues (Val243 and Leu2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…The analysis of three Vp3 mutants (F157E-I158E, P164E-G165R-G166E, and P164R-P165E-P166R) and three Vp1 mutants (V243E, L245E, and V243E-L245E) by transfection of the mutant viral genomes into host monkey kidney cells showed that all of the mutants replicate viral DNA and produce capsid proteins normally. However, the mutants are much less infectious than the wild type (41). A plausible interpretation of these data is that the capsids of these particles comprise Vp1 but little or no Vp2/3 owing to compromised Vp1-Vp3 interaction.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…The analysis of three Vp3 mutants (F157E-I158E, P164E-G165R-G166E, and P164R-P165E-P166R) and three Vp1 mutants (V243E, L245E, and V243E-L245E) by transfection of the mutant viral genomes into host monkey kidney cells showed that all of the mutants replicate viral DNA and produce capsid proteins normally. However, the mutants are much less infectious than the wild type (41). A plausible interpretation of these data is that the capsids of these particles comprise Vp1 but little or no Vp2/3 owing to compromised Vp1-Vp3 interaction.…”
mentioning
confidence: 82%
“…Most mutants are noninfectious (41), so the formation of mutant particles requires cells to be transfected with mutant DNAs, which are then isolated as described previously (27). Briefly, lysates from 5 ϫ 10 6 to 1 ϫ 10 7 cells that had been transfected with mutant DNAs were separated by sedimentation through sucrose gradients, and the presence of particles in the fractions was determined by anti-Vp1 Western blotting using 1/50 of each fraction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both domains are required for the membrane association and disruption activity found with VP4. In the context of VP2 and VP3, the HD from VP4 serves as the VP1 binding domain that supports virus assembly by binding to the hydrophobic central cavity within VP1 pentamers (2,11,41). The basic amino acid cluster, or the NLS, directs the trafficking of the late proteins to the nucleus (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Vp2 and Vp3 are required for the transport of the infecting viral DNA to the cell nucleus (5,7). Vp1 is necessary for the packaging of the viral minichromosome and assembly of the capsid and mediates cell attachment and entry (5,6). Thus, the formation of infectious SV40 virions depends on the proper folding of the newly synthesized Vp1 into the functional building block of the capsid, namely, the Vp1 pentamer.…”
mentioning
confidence: 99%